2014
DOI: 10.1016/j.bmc.2014.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new selective dopamine D4 receptor ligand

Abstract: The dopamine D4 receptor has been shown to play key roles in certain CNS pathologies including addiction to cigarette smoking. Thus, selective D4 ligands may be useful in treating some of these conditions. Previous studies in our laboratory have indicated that the piperazine analog of haloperidol exhibits selective and increased affinity to the DAD4 receptor subtype, in comparison to its piperidine analog. This led to further exploration of the piperazine moiety to identify new agents that are selective at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 36 publications
0
53
0
Order By: Relevance
“…Using the previously reported alkylating agent 2-(2-chloroethyl)-5-fluoro-2,3-dihydro-1H-inden-1-one ( 25 ), 20, 21 THIQ was alkylated under alkylation method B to afford compound 3h in 23% yield. Mp 240-241 °C; 1 H NMR (DMSO- d 6 ): 7.73 (dd, J = 5.8, 8.4 Hz, 1H), 7.45 (d, J = 9.0 Hz, 1H), 7.24 (m, 5H), 4.52 (m, 2H), 4.28 (m, 2H), 3.68 (m, 1H), 3.34 (m, 6H), 2.99 (m,1H), 2.89 (m, 2H), 2.31 (m, 1H), 1.99 (m, 1H).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the previously reported alkylating agent 2-(2-chloroethyl)-5-fluoro-2,3-dihydro-1H-inden-1-one ( 25 ), 20, 21 THIQ was alkylated under alkylation method B to afford compound 3h in 23% yield. Mp 240-241 °C; 1 H NMR (DMSO- d 6 ): 7.73 (dd, J = 5.8, 8.4 Hz, 1H), 7.45 (d, J = 9.0 Hz, 1H), 7.24 (m, 5H), 4.52 (m, 2H), 4.28 (m, 2H), 3.68 (m, 1H), 3.34 (m, 6H), 2.99 (m,1H), 2.89 (m, 2H), 2.31 (m, 1H), 1.99 (m, 1H).…”
Section: Methodsmentioning
confidence: 99%
“…Under the general alkylation method B , the previously described alkylating agent 2-(2-chloroethyl)-2,3-dihydro-1H-inden-1-one ( 26 ) 20 was coupled to THIQ to afford compound 3i as the HCl salt in 65% yield. Mp: 201-203 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ML398 has been presented as a selective D4 antagonist in recent studies [10]. Moreover, some selective ligands exhibited remarkable binding affinity to 5HT 1A R ,5HT 2A R, and 5HT 2B R [11,12]. A SAR study of selective D4 ligands reported an important arene-cation interaction between the ligands arene moiety and the residue Arg-186.…”
Section: Introductionmentioning
confidence: 99%